The Impact of Financial Planning on Financial Performance of SMEs. A Case Study of Coca Cola Beverages, Namanve - Sharif Ssewanyana (Uganda Christian University, 2026)
This study sought to investigate the impact of financial planning on the financial performance of Small and Medium Enterprises (SMEs), using Coca-Cola Beverages based in the Namanve Industrial Area as the focal point of the study. This was informed by the following objectives:examining the impact of budgeting practices on financial performance, evaluating the impact of cash flow management on financial performance, and examining the impact of financial planning on financial performance. Financial performance was evaluated using parameters such as profitability, liquidity, and solvency, while financial planning was evaluated using parameters such as budgeting, cash flow management, and capital expenditure planning. A descriptive and correlational research design was employed to establish the link between financial planning and financial performance. A population of 120 employees from various departments, including accounting, finance, marketing, and administration, was targeted. A sample of 70 respondents was established using Krejcie and Morgan’s sampling table. Stratified random sampling and simple random sampling methods were employed to ensure proper representation of respondents from various departments. Both primary and secondary data collection methods were employed. Under primary data, structured questionnaires were used as a means of collecting data. Secondary data was obtained from various records and relevant documents. Descriptive statistics, including frequency, percentage, means, and standard deviation, were employed to analyze the obtained data with the aid of Statistical Package for Social Sciences (SPSS). The results indicated that effective budgeting enhances financial performance by improving cost control, resource allocation, and profitability. Moreover, the study established that effective cash flow management is critical in ensuring that organizations are able to meet their financial obligations. Finally, the study established that financial planning has a strong positive relationship with financial performance, thus showing that organizations that employ effective financial planning are more likely to attain financial stability and success. The study concludes that financial planning is a critical strategy that can improve financial performance in SMEs. Effective budgeting, cash flow management, and financial decision making can improve efficiency and sustainability of organizations. Therefore, this study recommends that SMEs should improve their financial planning by employing effective budgeting techniques, cash flow management, and financial management skills to improve theirbusiness performance.
Undergraduate research